Strategic Planning and Relationship with Achieving the quality assurance level in faculty of education from the view point of the Teaching Staff Members - Afield Study at Tishreen University - Mohamed , Mahmoud; Mahmoud , Noura (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The current research aims to identify the degree of Practicing Strategic Planning of and the degree of the quality assurance level in faculty of education at Tishreen University from the view point of the Teaching Staff Members, and also and to study the relationship between the degree of Practicing Strategic Planning and quality assurance level in it. and to achieve the objectives of this research questionnaires were built, the first about strategic planning included four areas, and consisted (50) items, while the second about quality assurance consisted (20) items; have been applied on sample (72) Teaching Staff Members in faculty of education at Tishreen University during the academic year of (2016 - 2017). Descriptive analytical methodology was used, and Validity of the questionnaire was established though a jury of (7) of the teaching staff at Syrian Universities. Pilot sample consisted of (22) Members, Reliability was established by Cronbach – Alpha Reliability (0.87) to Strategic Planning questionnaire and (0.73) to quality assurance questionnaire. The research results showed that the degree of Practicing Strategic Planning, and the degree of the quality assurance level at faculty of education at Tishreen University were middle rated from the view point of the Teaching Staff Members, also results showed there is a positive correlation between the degree of Practicing Strategic Planning and quality assurance level in faculty of education at Tishreen University. In fact the study included some of recommendations: The need to provide human and material resources to practice of strategic planning in faculty of education at Tishreen University, and developing the workers performance throw preparing training to workers at faculty of education, correlate with Strategic Planning, and continuous enlightenment with Strategic Planning an importance in Achieving the quality assurance level.